Time management on task completion of science, technology, engineering, and mathematics (STEM) students of ECT Excellencia Global Academy Foundation, Inc. - Shanzee Marie Jayme; Michael Aparecio; Alan A. Bendanillo; Andre Mari M. Arana; Jeain Philip Dumdum; Nanami Ikeshiro; Ked Toring (Science and Education, 2023)
Time management is a collection of skills that you may use to make the most of your time and enhance your quality of life. Most commonly, students would find meaning, accomplishment, and even fulfillment once achieved the objectives that they set. This is possible because they wisely manage their time. Henceforth, this research study will shed light a report on the concept of time management that significantly affects towards the STEM students’ of ECT Excellencia Global Academy Foundation, Inc. (EEGAFI) on their potentiality to complete their tasks on time. To determine the limitations of students’ time management, hypotheses were developed along with the problems and objectives of this study. The respondents of this study were from the students of STEM 11 of EEGAFI. 150 respondents were randomly selected and these students were those who volunteered to participate in the surveys were picked at random from the group. The researchers gave the predetermined questionnaires to the respondents in this research study with the primary goal of collecting data for statistical analysis. The findings showed that time management behaviors such as procrastination, prioritizing, and planning had a significant impact on the task completion of the students. When doing task completion, it is advised that students pay close attention to the passing of time. Efforts to ensure strong academic success. Given that procrastination, when compared to other factors, significantly affects academic achievement, the results show that students need work very hard to finish their projects as well as completing all other academic tasks on time to avoid missing deadlines.